Data acquisition system: on the solar photovoltaic module and weather parameters monitoring - Benlebna, Soumia; Kumar, Nallapaneni Manoj; Tahri, Ali (Elsevier, 2018)
This paper deals with a study on the data acquisition system (DAS) used for monitoring the solar photovoltaic cell/module/array parameters as well as the weather parameters. The need for facilitating DAS for photovoltaic applications is clearly evaluated based on the few practical studies taken from the literature. A system setup combining the instruments and measurement equipment required as per the objective of the study (required for selected parameters as in the user defined objective) is proposed for PV applications as well as for weather monitoring. Various parameters and their implications on the system output is clearly stated. A case study describing the Algerian PV + Weather monitoring station is discussed by highlighting the system design and its functionality in monitoring parameters. Possible research option with the monitored data from the photovoltaics and weather parameters is also listed. The paper is concluded focusing on the need and benefits of DAS and monitoring facilities for PV applications.